Description of female of Oxybelochardus iraqensis Hamodee and Shafeeq, 2023 (Hymenoptera, Crabronidae) - Augul, Razzaq Shalan; Hamodee, Shatha Abdullateef (Zootaxa, 2025)
The female of Oxybelochardus iraqensis (Hymenoptera: Crabronidae) is described and illustrated for the first time based on the material collected in Iraq.